New values for mr(2,29) and tr(2,29) in PG(2,29) - Nada Yassen Kasm Yahya; Shuaa Aziz (College of Education for Pure Sciences, 2010)
ABSTRACT In this paper we find the nearest complete(n,r)-arcs of the maximum value for mr(2,29)-arc when . Also, we find the nearest minimum size of complete tr(2,29)-arcs when ,as well as we set some open questions concerning for non-existence of complete (n,r)-arcs. All this done by a computer program, noteworthy that there is no results published till now when for mr(2,29) and there are no results published till now for tr(2,29) when in PG(2,29) (according to the knowledge of the authors).